Blue-Light Levels Emitted from Portable Electronic Devices Compared to Sunlight - David Baeza Moyano; Yolanda Sola; Roberto Alonso González-Lezcano (Energies, 2020)
Over recent years, a technological revolution has taken place in which conventional lighting has been replaced by light emitting diodes (LEDs). Some studies have shown the possibility that blue light from these artificial sources could have deleterious effects on the retina. Considering that people spend a non-negligible time in front of screens from computers and mobile phones, the eyes receive blue light of different intensities depending on the source. Nevertheless, any study about the visual and non-visual effects of blue light must consider precise measurements taken from actual artificial sources. For this reason, we have analyzed the spectral emission of 10 different electronic devices and weighted them according to the hazard caused by blue light to the eyes, comparing the results with solar radiation simulated with a radiative transfer model. The maximum spectral irradiance of the measured electronic devices at 10 cm from the detector was located between 440 nm and 460 nm. The irradiance for blue light hazard ranged from 0.008 to 0.230 Wm−2 depending on the particular characteristics of each electronic device. In contrast, the solar radiances in the same spectral range are larger both under clear and cloudy conditions.